2017
DOI: 10.1039/c7qo00232g
|View full text |Cite
|
Sign up to set email alerts
|

The study of metal-free and palladium-catalysed synthesis of benzochromenes via direct C–H arylation using unactivated aryl benzyl ethers derived from essential oils as raw materials

Abstract: The synthesis of 6H-benzo[c]chromenes, from phenol-rich essential oils, was studied through two approaches, establishing the Pd-approach as the most efficient protocol over the metal-free process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…We noticed that Ma's group reported that the addition of carboxylic acids accelerated and improved the yields of C1-alkynylation of THIQs during the enantioselective version of this reaction, without evidence of the formation of the side propargylamine 8a derivative. 37 Based on this finding and also our previous experiences, 38 pivalic acid (5 mol%) was chosen as an additive but, under these reaction conditions, a low conversion into the desired 8a was observed (40%) and the kinetic propargylamine product 8a was also identified, in a 1.5:1 ratio (Table 3, entry 11). Next, we used benzoic acid as an additive, and although the 1alkynyl THIQ 8a was isolated in poor yield (20%), the propargylamine was not identified and the desired 8a was exclusively obtained (entry 12).…”
Section: Couplingmentioning
confidence: 81%
“…We noticed that Ma's group reported that the addition of carboxylic acids accelerated and improved the yields of C1-alkynylation of THIQs during the enantioselective version of this reaction, without evidence of the formation of the side propargylamine 8a derivative. 37 Based on this finding and also our previous experiences, 38 pivalic acid (5 mol%) was chosen as an additive but, under these reaction conditions, a low conversion into the desired 8a was observed (40%) and the kinetic propargylamine product 8a was also identified, in a 1.5:1 ratio (Table 3, entry 11). Next, we used benzoic acid as an additive, and although the 1alkynyl THIQ 8a was isolated in poor yield (20%), the propargylamine was not identified and the desired 8a was exclusively obtained (entry 12).…”
Section: Couplingmentioning
confidence: 81%
“…A few representative examples of direct C-H arylation in 1-butyl-3-methylimidazolium hexafluorophosphate were also reported in 2017 by Kouznetsov and co-workers in the context of the synthesis of 6H-benzo [c]chromenes by intramolecular ortho-arylation of chloro-and bromo-aryl benzyl ethers. 269 Interestingly, also in these cases reactions were carried out under transition metal-free conditions, in the presence of potassium t-butoxide (3.0 equiv.) as the base and phenanthroline (20 mol%) acting as an organocatalyst through a radical mechanism.…”
Section: Direct C-h Bond Arylation Of (Hetero)arenes In Ionic Liquids...mentioning
confidence: 99%
“…Considering the potential use of DESs and essential oils in organic synthesis and in continuation with our studies focused on the development of sustainable methodologies for the obtention of valuable organic compounds, in this contribution, we wish to report a new, sustainable, simple, and efficient method for the diastereoselective synthesis of tetrahydroquinoline derivatives from star anise oil, anilines, and aromatic aldehydes in the presence of the choline chloride/zinc chloride DES via the IEDDA reaction.…”
Section: Introductionmentioning
confidence: 99%